2014
DOI: 10.1002/mrd.22350
|View full text |Cite
|
Sign up to set email alerts
|

Viable and morphologically normal boar spermatozoa alter the expression of heat‐shock protein genes in oviductal epithelial cells during co‐culture in vitro

Abstract: The principal aim of this study was to determine if boar spermatozoa influence the expression of four selected chaperone and heat-shock protein (HSP) genes-namely clusterin (CLU), HSP90AA1, HSPA5, and HSPA8-in oviductal epithelial cells (OECs) during in vitro co-culture. All corresponding proteins of these genes were previously identified in a sperm-interacting, 70-kDa soluble fraction derived from apical plasma membranes of OECs. The present study also sought to determine whether or not: (i) spermatozoa must … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…A later study in mice found that insemination induced de novo gene transcription in the female reproductive tract, stimulated specifically by spermatozoa and not by seminal plasma [61]. These results were later confirmed by both in vitro and in vivo experiments involving insemination responses in pigs and cattle [62][63][64][65][66]. Interestingly, similar responses to the arrival of spermatozoa have also been noted in avian sperm storage glands [67][68][69].…”
Section: Oviductal Responses To Sperm Entrymentioning
confidence: 72%
See 1 more Smart Citation
“…A later study in mice found that insemination induced de novo gene transcription in the female reproductive tract, stimulated specifically by spermatozoa and not by seminal plasma [61]. These results were later confirmed by both in vitro and in vivo experiments involving insemination responses in pigs and cattle [62][63][64][65][66]. Interestingly, similar responses to the arrival of spermatozoa have also been noted in avian sperm storage glands [67][68][69].…”
Section: Oviductal Responses To Sperm Entrymentioning
confidence: 72%
“…It appears that the process is initiated rapidly, with changes being detectable within 1 hour [66]. Moreover, the importance of direct contact between oviductal epithelial and spermatozoa in initiating gene expression responses was demonstrated by in vitro studies, where porcine oviductal epithelial cells failed to initiate the production of heat shock proteins when direct contact was prevented [65].…”
Section: Oviductal Responses To Sperm Entrymentioning
confidence: 99%
“…It has neither been lost nor duplicated in the sampled species, contrary to HSPA8, which was duplicated in orangutan, rat, sheep, and pig. Heat shock proteins A5 and A8 play a role in the modulation of boar sperm function in the oviductal reservoir (Yeste et al 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Yeste et al and Moein-Vaziri et al showed that when epithelial cells in the oviduct are co-cultured with viable spermatozoa, the gene expression profile of these epithelial cells is altered. These changes coincide with the restoration of sperm membrane integrity and fluidity that are essential for sperm capacitation [47, 48]. Based on morphology, the oviduct can be subdivided into four segments, the uterotubulo junction, isthmus, ampulla, and infundibulum (from the uterus toward the ovary); each segment contains similar sorts of cells, but in different proportions.…”
Section: Modifications Of the Sperm Membrane Surface By The Female Rementioning
confidence: 99%